The Fit of Safety Helmet Among Female - Mustafa El Bakri, Helmy; Nasir, Siti Hana; Lukeman, Nur Izzah (Progress in Engineering Application and Technology, 2020)
Safety helmets are used in many fields of endeavour such as police work, fire fighting, construction work, and sports as well as by aircraft crew members. Safety helmets are protective equipment used to reduce or prevent the impact on the head when an object is hit or dropped. With the proper and right way of helmet used, it acts as a protection tool for workers and can help prevent and control collateral damage. This pilot research study the fit and comfort perception of safety helmet among women participants. The method used in this reseach was collecting data from questionnaires, scanning the participants head when wearing and not wearing a safety helmet, post-scanning data processing and data of gap analysis, proportion of head under helmet protection and HFI calculation. 5 out of ten participants were feeling discomfort when wearing safety helmets. The left, right, top and front regions of the head have a larger gap compared to the back region. The overall HFI score was middle fit.